PROCESSING RED GINGER INTO SYRUP TO IMPROVE HEALTH AND FAMILY ECONOMY IN COT MESJID VILLAGE, LUENG BATA DISTRICT - Chudri, Intan Rizkia; Purnamasari, Desy (ABDIMU: Jurnal Pengabdian Muhammadiyah, 2024)
Red Ginger is popularly consumed worldwide as a pleasant drink and for its health benefits, which are largely due to its composition. The utilization of Red Ginger has not been maximized. Most people are not interested in red ginger because it tastes bad and do not know much about how to process it. Red Ginger contains good nutritional composition for health such as containing mineral elements including potassium, sodium, calcium, magnesium, phosphorus, chlorine and a number of vitamins although in small amounts. This Red Ginger has been processed into several products such as flavorings in food, compositions in herbal medicine. For this reason, it is necessary to diversify processed products from red ginger such as making syrup. The method of implementing community service is by conducting training on how to make syrup from red ginger. Syrup from red ginger is an innovation from agricultural products that can be processed into something that has high economic value.Keywords : Red Ginger, Syrup, Improves Family Health and Economy